Voice Structure used in Advertisements - Mousa, Abdulwahab K.; Abdullah, Abdulsalam N. (Humanities Journal of University of Zakho, 2015)
The research is about the voice structure used in advertisings, means it searches for that voice arts used in Kurdish advertisings and how by this they try to make persuasion which means the research is on phonologic level of advertisings. This research in general has been done according on the descriptive and analytical approach.For doing this research the researcher has put a hypothesis which is a parallelism and deviation and are known as two techniques for foregrounding of daily speech and avoiding automatic language (poetic function) have Kurdish advertising used this two techniques or not? If the answer is yes, the average of each is how much? The researcher has tied to prove it by static. At the end the researcher has found that in about 75% poetic function is used and of this 92% is parallelism and 35% is deviation, and this indicate that in Kurdish advertisings they given importance in giving them musical form. Parallelism has made by repeating compared to deviation which need more specialty